Analisis Dan Perancangan Sistem Informasi Pendistribusian Gas LPG Bersubsidi Pada PT. Andalan Putra Jambi - Putra, Rona; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2020)
In the data processing process of subsidized LPG (Liquified Petroleum Gasses) gas distribution at PT. Andalan Putra Jambi, faced with several obstacles, including the frequent recording of payment errors, the slow provision of information if needed, difficult to be controlled by the leader quickly and in real time because there is no information base owned and efforts are needed to ensure that the distribution is right on target to the community has the right to use subsidized LPG gas. For this reason, this study aims to analyze the business needs of the system requirements and design an information system for subsidized LPG gas distribution at PT. Andalan Putra Jambi uses the method of analysis and design of the mode; l waterfall and utilizes an analytical aid namely UML (Unified Modeling Language) as well as the design of a prototype system using PHP programming language and MySQL database management system. The results of this study are expected to be implemented and can help interested parties at PT. Andalan Putra Jambi in seeing and assessing the extent to which the results of the analysis and design in this study have represented the needs of users. The design of the system produced in this study can be applied to other similar companies with adjustments as needed and for other researchers who will conduct research in the same case it is expected to review the government policies in the distribution of subsidized LPG Gas.